2008
DOI: 10.1002/clen.200700182
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Recovery of Surrogates for Bacterial Bioterrorism Agents from Ventilation Filters

Abstract: Heating, ventilating, and air-conditioning (HVAC) filters have the potential to serve as long-term integrated samplers for biological particles that may be released intentionally or unintentionally into a public building. Methods for eluting bacteria that are surrogates for potential bioterrorism agents from HVAC filters were tested for their ability to recover as high a percentage of culturable bacteria as possible. A solution of 0.02% Tween-80 in water was an effective eluent for Bacillus globigii (BG) spore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Improved recovery due to the addition of Tween 80 in wetting agent and extraction solutions has been associated with high environmental sampling performance (Kim et al . ; Da Silva et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved recovery due to the addition of Tween 80 in wetting agent and extraction solutions has been associated with high environmental sampling performance (Kim et al . ; Da Silva et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…All wetting agents utilized in this work containing Tween 80 (T80 and PBST) resulted in the best recovery efficiency (RE soln ) when compared with the other wetting agents by rank analysis (Table 2). Improved recovery due to the addition of Tween 80 in wetting agent and extraction solutions has been associated with high environmental sampling performance (Kim et al 2008;Da Silva et al 2011). In the current study, spores were likely entrapped in the wipe fibres contributing to the low release of spores from the wipes.…”
Section: Discussionmentioning
confidence: 99%
“…Edwards et al (2004) showed similar extraction efficiencies of MS2 from FFR coupons by vortexing and by shaking. Kim et al (2008) showed that shaking gave twice higher efficiency than vortexing BG spores into ATCC medium (organic matter). The suggestion from these limited examples is that the efficiency may be both species and medium dependent.…”
Section: A32 Determination Of Extraction Conditionsmentioning
confidence: 99%
“…The first one (Kim, Raynor, Kuehn, Goyal, Ramakrishnan, Anantharaman, and Farnsworth of the University of Minnesota, USA) considers heating, ventilating, and air-conditioning (HVAC) filters as long-term integrated samplers of biological particles, which may be released intentionally or unintentionally into a public building [12]. While bacterial spores were shown to much more likely maintain their culturability than vegetative bacterial cells during filtration on HVAC filters, the authors demonstrated that the vegetative cells could be successfully eluted from HVAC filters even if they do not maintain their culturability.…”
Section: Topical Issue: Bioaerosol Researchmentioning
confidence: 99%